2010
DOI: 10.1016/j.chemolab.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Drift compensation of gas sensor array data by Orthogonal Signal Correction

Abstract: Drift is an important issue that impairs the reliability of gas sensing systems. Sensor aging, memory effects and environmental disturbances produce shifts in sensor responses that make initial statistical models for gas or odor recognition useless after a relatively short period (typically few weeks). Frequent recalibrations are needed to preserve system accuracy. However, when recalibrations involve numerous samples they become expensive and laborious. An interesting and lower cost alternative is drift count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(110 citation statements)
references
References 37 publications
0
110
0
Order By: Relevance
“…Indeed, in spite of constant improvements in micro/nanofabrication techniques that allowed the production of sensing devices with superior stability, it is still impossible to fabricate chemical sensors without drift. This issue is currently approached on one hand by improving the sensors performances with novel sensing materials [59], on the other hand by adopting various approaches for compensating sensors drift to increase pattern recognition accuracy [60,61].…”
Section: Discussion and Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in spite of constant improvements in micro/nanofabrication techniques that allowed the production of sensing devices with superior stability, it is still impossible to fabricate chemical sensors without drift. This issue is currently approached on one hand by improving the sensors performances with novel sensing materials [59], on the other hand by adopting various approaches for compensating sensors drift to increase pattern recognition accuracy [60,61].…”
Section: Discussion and Issuesmentioning
confidence: 99%
“…These can be both thick-film commercial Taguchi sensors (TGS2611 and TGS2442 were employed for instance by Cagnasso et al [13]) or home-made thin-film sensors (further details can be found in Comini et al [60] and references therein) among which tin oxide, often catalyzed with noble metals (e.g., Au, Ag, Pt, Pd, or Mo), and other metal oxides like tungsten oxide are commonly used.…”
Section: Eos Electronic Nose Descriptionmentioning
confidence: 99%
“…Nevertheless, these methods can sometimes mistakenly update the pattern by following the wrong reference class. Component Correction-(CC-) based methods are said to have good results [25][26][27]. However, they assume that the gases behave in a similar way in the drift process, while the truth is quite the opposite.…”
Section: Analytical Model For Drift Compensationmentioning
confidence: 99%
“…The common methods used for extracting drift signals include Principal Component Analysis (PCA), (6)(7)(8) Independent Component Analysis (ICA), (9) and Partial Least-Squares (PLS). (10) Aside from these methods, the Orthogonal Signal Correction (OSC) is superior to drift correction as shown in a recent study by Padilla et al (11) Generally speaking, all the component correction methods aim to find one preferable direction to eliminate drift. However, the drift direction varies with time and gas type in the mapping space, (6) and consecutive groups of samples are needed for predicting each drift direction.…”
Section: Introductionmentioning
confidence: 99%